Charles Taylor’s Ideal of Modern Identity in the Context of the "Liquid Modernity" Realities - Liakh, V. V (Anthropological Measurements of Philosophical Research, 2022)
Purpose. The article aims, through a comparison of the modern identity as presented in Charles Taylor’s concept with the Postmodern era identities, to show the strengths and weaknesses of Charles Taylor’s position on preserving or prolonging the Modern era identity to our time, as well as to define the specifics of liquid modernity compared to the New Age. Theoretical basis. Given the relevance of the topic of the human search for authentic existence in the modern world, the author analyzes Taylor’s belief that the moral ideal of authentic identity emerged in the New Age. This ideal to contrast the idea of it in the previous periods is not set from the outside but is formed or created by a human himself. In addition, it is so powerful and productive that it must be fought for nowadays. After Taylor, since the existence of modern people tends to experience negative distortions associated with the focus on consumer individualism, instrumental thinking, and their loss of political freedom, the only possible way out is to turn to the ideal of authenticity of modern times. However, the article emphasizes that the modern studies of the Second Modernity (U. Beck) or liquid modernity (Z. Bauman) show a rather radical change in social reality, which, accordingly, requires new types of identity. Originality. The article argues that the identity formed in the New Age had signs of authenticity only owing to the socio-economic system of the time that formed a human as a self-acting being who determines his or her destiny. This person was characterized by such traits as individualism, self-sufficiency, self-reliance, victory, heroism, and so on. However, the article emphasizes that today the situation has changed radically, as the reality of the Postmodern era is characterized by the fact that instead of stable, clearly defined life forms and institutions we are dealing with changing, fluid, "liquid" (Z. Bauman) institutions and behaviours of people. Diversity, uncertainty, and pluralism are the hallmarks of this era that need to be taken into account in one way or another. Therefore, although Taylor’s arguments for defending the modern identity are logically invulnerable, they have the disadvantage of not taking into account the irreversibility of the changes that have taken place in modern reality. Therefore, the ideal of authenticity formed in the New Age may not be adequate in the times of pluralism and the development of other dimensions of identity. Conclusions. Taylor’s interpretation of modern authenticity was based on the idea of man as one who constantly constructs himself and is focused on the future, which we can imagine, plan and make some effort to achieve. This position of Taylor is criticized in the article. I substantiate the view that both the moral ideal and its components can change in the process of historical development. This becomes clear if we take into account the gap that manifested itself in the shift of value orientations during the transition from the Modern to the Postmodern era. Nowadays, we have a process of changing the basic conditions that determined the identity of a modern human, and the formation of new basic conditions that are suggested as requiring identity redefinition in a post-industrial network society.